Crime and punishment in Latin America : law and society since late colonial times - Salvatore, Ricardo Donato; Aguirre, Carlos, 1958-; Joseph, G. M. (Gilbert Michael), 1947- (Duke University Press, 2001)
Essays in collection argue that Latin American legal institutions were both mechanisms of social control and unique arenas for ordinary people to contest government policies and resist exploitation.